2014
DOI: 10.3389/fpsyg.2014.00708
|View full text |Cite
|
Sign up to set email alerts
|

Measuring inconsistencies can lead you forward: Imageability and the x-ception theory

Abstract: According to the traditional view, both imageability and concreteness ratings reflect the way word meanings rely on information mediated by the senses. As a consequence, the two measures should and do correlate. The link between these two indexes was already hypothesized and demonstrated by Paivio et al. (1968) in a seminal article, where they introduced the idea of imageability ratings for the first time. However, in this first study, they also noted a contrasting pattern in the ratings for imageability and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
40
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 41 publications
12
40
0
3
Order By: Relevance
“…Of special note, the database includes 4,295 words rated with degrees of abstractness, these ratings ranging from 158 (meaning highly abstract) to 670 (meaning highly concrete), and also 9,240 words rated for degrees of imageability, which can be defined as how easily a word can evoke mental imagery, these ratings also ranging between 100 and 700 (a higher score indicating greater imageability). It should be noted that it has long been known that the concreteness and imageability scores are highly correlated (Paivio et al, 1968), however, there are interesting differences between these sets of scores (Dellantonio et al, 2014), and we are currently investigating these differences in further studies (see Section (4) below). These scores have been used extensively for work that is similar to ours, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Of special note, the database includes 4,295 words rated with degrees of abstractness, these ratings ranging from 158 (meaning highly abstract) to 670 (meaning highly concrete), and also 9,240 words rated for degrees of imageability, which can be defined as how easily a word can evoke mental imagery, these ratings also ranging between 100 and 700 (a higher score indicating greater imageability). It should be noted that it has long been known that the concreteness and imageability scores are highly correlated (Paivio et al, 1968), however, there are interesting differences between these sets of scores (Dellantonio et al, 2014), and we are currently investigating these differences in further studies (see Section (4) below). These scores have been used extensively for work that is similar to ours, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Although these subjective variables are not independent from each other, an increasing body of studies suggest that they theoretically and empirically constitute distinct constructs (e.g., Connell & Lynott, 2012;Dellantonio, Mullatti, Pastore, & Job, 2014;Kousta et al, 2011). For example, although imageability is highly correlated with concreteness (.83 in Paivio's work and around that value in subsequent studies-e.g., Altarriba et al, 1999;Connell & Lynott, 2012;Gilhooly & Logie, 1980;Toglia & Battig, 1978), which has supported the interchangeable use of both measures in experimental research (see, e.g., Fliessbach, Weis, Klaver, Elger, & Weber, 2006), a growing body of evidence has suggested that imageability and concreteness capture different word properties (e.g., Connell & Lynott, 2012;Dellantonio et al, 2014;Kousta et al, 2011).…”
mentioning
confidence: 99%
“…U novije se vrijeme neki istra`iva~i vra}aju emocionalnoj obojenosti (npr. Altarriba, Bauer i Benvenuto 1999), dok Dellantonio i suradnici (Dellantonio et al 2014) pak pro{iruju navedeni zaklju~ak te pokazuju da se konkretnost i predo~ivost ne razlikuju samo kod rije~i koje su emocionalno obojene nego i kod onih koje se odnose na proprioceptivno i interoceptivno iskustvo (npr. rije~i poput glad, koja se odnosi na unutarnje osjetilno iskustvo, za razliku od rije~i slan, koja se odnosi na izvanjsko osjetilno iskustvo).…”
Section: Odnos Konkretnosti I Predo~ivostiunclassified
“…I u na{oj se bazi, kao i u dosada{njim istra`ivanjima, uo~avaju primjeri rije~i niske konkretnosti, a visoke predo~ivosti. Razlika u veli~ini korelacije izme|u konkretnosti i predo~ivosti za apstraktne i konkretne rije~i u skladu je s rezultatima koje su dobili Dellantonio et al (2014). Ipak, neformalnim uvidom u to koje su rije~i u na{oj bazi procijenjene kao niskokonkretne, a visokopredo~ive te sude}i prema njihovu malenom broju, ne ~ini se da je ta razlika sasvim u skladu s rezultatima vezanima uz proprioceptivno i interoceptivno iskustvo (kao {to tvrde Dellantonio et al 2014).…”
Section: Raspravaunclassified
See 1 more Smart Citation